Widespread microRNA dysregulation in multiple system atrophy – disease‐related alteration in miR‐96. (5th December 2013) - Ubhi, Kiren; Rockenstein, Edward; Kragh, Christine; Inglis, Chandra; Spencer, Brian; Michael, Sarah; Mante, Michael; Adame, Anthony; Galasko, Douglas; Masliah, Eliezer
Abstract MicroRNA (miRNA) are short sequences of RNA that function as post‐transcriptional regulators by binding to target mRNA transcripts resulting in translational repression. A number of recent studies have identified miRNA as being involved in neurodegenerative disorders including Alzheimer's disease, Parkinson's disease and Huntington's disease. However, the role of miRNA in multiple system atrophy (MSA), a progressive neurodegenerative disorder characterized by oligodendroglial accumulation of alpha‐synuclein remains unexamined. In this context, this study examined miRNA profiles in MSA cases compared with controls and in transgenic (tg) models of MSA compared with non‐tg mice. The results demonstrate a widespread dysregulation of miRNA in MSA cases, which is recapitulated in the murine models. The study employed a cross‐disease, cross‐species approach to identify miRNA that were either specifically dysregulated in MSA or were commonly dysregulated in neurodegenerative conditions such as Alzheimer's disease, dementia with Lewy bodies, progressive supranuclear palsy and corticobasal degeneration or the tg mouse model equivalents of these disorders. Using this approach we identified a number of miRNA that were commonly dysregulated between disorders and those that were disease‐specific. Moreover, we identified miR‐96 as being up‐regulated in MSA. Consistent with the up‐regulation of miR‐96, mRNA and protein levels of members of the solute carrier protein family SLC1A1 and SLC6A6, miR‐96 target genes, were down‐regulated in MSA cases and a tg model of MSA. These results suggest that miR‐96 dysregulation may play a role in MSA and its target genes may be involved in the pathogenesis of MSA.